PERBEDAAN EMESIS GRAVIDARUM SEBELUM DAN SETELAH TERAPI AKUPRESUR PADA TITIK PC 6 (NEIGUAN) - Juliani, Ni Made; Suindri, Ni Nyoman; Wirata, I Nyoman (ARCHIVE OF COMMUNITY HEALTH, 2023)
ABSTRACT Emesis gravidarum is nausea and vomiting experienced by mothers during pregnancy. Poor maternal nutritional status during pregnancy is associated with low birth weight, maternal and perinatal mortality. The aim of this study was to determine the differences in emesis gravidarum before and after acupressure therapy at PC 6 (Neiguan). This research is a Pre-Experimental The One Group PreTest-PostTest Design. Total respondents 28 people. Sampling using purposive sampling method. Primary data obtained from the results of the PUQE-24 questionnaire. Data analysis with Wilcoxon test. Median pretest results 2.00 and median posttest 1.00, Wilcoxon test with Asymp. Sig 0.00. There are differences in emesis gravidarum before and after acupressure therapy at PC 6 (Neiguan) point. Acupressure therapy at point PC 6 (Neiguan) can reduce emesis gravidarum in first trimester pregnant women. Recommendations for future researchers to conduct multivariate tests on predisposing factors so as to get a more detailed picture of the results related to factors that can lighten or exacerbate the value of the dependent variable. Keywords: Acupressure; Emesis Gravidarum; PUQE-24